Hate on the net extremist sites, neo-fascism on-line, electronic jihad - Roversi, Antonio (Advances in criminology, 2008)
An analysis of websites that incite violence, both symbolic and real, and act as a conduit for messages which promote racism, xenophobia, antisemitism and, in one case, incitement to armed warfare.